Analisis Karakteristik Tegangan Tembus Isolasi Minyak Transformator Menggunakan Oli Sepeda Motor Shell Advance 20w-50 Dan Pertamina Mesran 20w-50 - Adi Purwanto Umar; Sutiyono Hulopi; Lanto Mohamad Kamil Amali (Politeknik Negeri FakFak, 2023)
Electrical systems use high-voltage insulation as a cooling agent. A breakdown voltage will show up to indicate insulation failure if the applied voltage is greater than the liquid insulation's dielectric strength. According to SPLN '50-1982 and IEC No. 56 of 1991, the typical breakdown voltage of PERTAMINA MESRAN transformer oil insulation at 30°C temperature before cleaning or treatment is 14.59 kV / 2.5 mm. Insulation of transformer oil is categorized as a sub-interest. (in a 30 Kv/2.5 mm manner). According to SPLN '50- 1982 and IEC No. 56 of 1991, the average breakdown voltage of PERTAMINA MESRAN transformer oil insulation at 300C temperature after cleaning/remediation process is 15.18kV / 2.5mm. Insulation of transformer oil is designated as standard ((standard). usually 2.5 mm/30 Kv). According to SPLN '50- 1982 and IEC No. 56 of 1991, the average breakdown voltage of SHE LL increase the oil-insulated transformer at 30°C temperature before cleaning / treatment Process is 16.52kV / 2.5mm. Transformer oil insulation (30Kv/2.5mm nominal) is viewed as being insufficient. According to SPLN'50-1982 and IEC No. 56 of 1991, the average breakdown voltage of SHELL formed transformer oil insulation at 30°C temperature after cleaning and treatment is 22.83 kV / 2.5 mm. A division below the standard (30 Kv / 2.5 mm is common) is transformer oil insulation.